UJI MACAM PUPUK ORGANIK TERHADAP PERTUMBUHAN DAN HASIL 2 VARIETAS TANAMAN STEVIA (Stevia rebaudiana Bertonii M) - Guzali, Futta Ifnu; Nurhayati, Dewi Ratna; Siswadi, Siswadi (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2020)
Research on Organic Fertilizer Tests on Growth and Yield of 2 Stevia Plant Varieties (Stevia rebaudiana Bertonii M)